2018
DOI: 10.1016/j.celrep.2018.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Clinical Relevance of Metabolic Expression Subtypes in Human Cancers

Abstract: SUMMARY Metabolic reprogramming provides critical information for clinical oncology. Using molecular data of 9,125 patient samples from The Cancer Genome Atlas, we identified tumor subtypes in 33 cancer types based on mRNA expression patterns of seven major metabolic processes and assessed their clinical relevance. Our metabolic expression subtypes correlated extensively with clinical outcome: subtypes with upregulated carbohydrate, nucleotide, and vitamin/cofactor metabolism most consistently correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
211
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(237 citation statements)
references
References 39 publications
15
211
0
Order By: Relevance
“…In all, 20 pathways were assessed (Table S1). These pathways were assembled from the curated lists by Peng et al (2018) [13], Fabregat et al (2016) [14], our previous comprehensive curation of pathways [17], and from KEGG [15] via the InnateDB platform (http://www.innatedb.com/) [16].…”
Section: List Of Genes In Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 20 pathways were assessed (Table S1). These pathways were assembled from the curated lists by Peng et al (2018) [13], Fabregat et al (2016) [14], our previous comprehensive curation of pathways [17], and from KEGG [15] via the InnateDB platform (http://www.innatedb.com/) [16].…”
Section: List Of Genes In Pathwaysmentioning
confidence: 99%
“…Metabolism pathways I -Clustering of PCa patients and initial analysis of pathways was performed using genes from amino acid metabolism (348), carbohydrate metabolism (286), lipid metabolism (766), tricarboxylic acid cycle (TCA cycle, 148), and vitamin & cofactor metabolism (168) pathways, the five main pathways listed in Peng et al [13].…”
Section: List Of Genes In Pathwaysmentioning
confidence: 99%
“…The main intrinsic factors that promote tumour growth usually contribute to abnormal expression of cell cycle-related proteins or metabolic genes in bladder cancer. 22,23 Therefore, we performed metabolic MS and RNA sequencing to identify the metabolic and molecular features of CARD10. The metabolomics data indicated that CARD10 mainly affects urea metabolism, especially nitrogen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Master regulators of carbohydrate and nucleotide metabolism showed consistently poor prognostic patterns across all analyzed cancer types whereas lipid metabolism showed the opposite association. 81 Accordingly, the expression of enzymes and transporters involved in glucose metabolism has been linked to unfavorable patient outcome in different tumor entities such as hepatocellular carcinoma, 82,83 melanoma 84,85 or urothelial carcinoma. 86 Moreover, in oral squamous cell carcinoma a high PET signal, thus a high glucose uptake, correlates with worse prognosis 83 and similarly, high intra-tumoral lactate concentration predicts the occurrence of metastases and patient survival.…”
Section: Of Oxygen As Low Ph Elicits a Transient And Reversible Loss mentioning
confidence: 99%